An investigation of volute cross-sectional shape on turbocharger turbine under pulsating conditions in internal combustion engine. (15th November 2015) - Yang, Mingyang; Martinez-Botas, Ricardo; Rajoo, Srithar; Yokoyama, Takao; Ibaraki, Seiichi
Highlights: Cycle averaged efficiency is higher for the volute A (low aspect ratio). More distorted flow in volute B is the reason for performance deterioration. Flow in volute B (high aspect ratio) is more sensitive to pulsating flow. Abstract: Engine downsizing is a proven method for CO2 reduction in Internal Combustion Engine (ICE). A turbocharger, which reclaims the energy from the exhaust gas to boost the intake air, can effectively improve the power density of the engine thus is one of the key enablers to achieve the engine downsizing. Acknowledging its importance, many research efforts have gone into improving a turbocharger performance, which includes turbine volute. The cross-section design of a turbine volute in a turbocharger is usually a compromise between the engine level packaging and desired performance. Thus, it is beneficial to evaluate the effects of cross-sectional shape on a turbine performance. This paper presents experimental and computational investigation of the influence of volute cross-sectional shape on the performance of a radial turbocharger turbine under pulsating conditions. The cross-sectional shape of the baseline volute (denoted as Volute B ) was optimized ( Volute A ) while the annulus distribution of area-to-radius ratio (A/R) for the two volute configurations are kept the same. Experimental results show that the turbine with the optimized volute A has better cycle averaged efficiency under pulsating flow conditions, for different loadings and frequencies. The advantage of performance is influenced by the operational conditions. After the experiment, a validated unsteady computational fluid dynamics (CFD) modeling was employed to investigate the mechanism by which performance differs between the baseline volute and the optimized version. Computational results show a stronger flow distortion in spanwise direction at the rotor inlet with the baseline volute. Furthermore, compared with the optimized volute, the flow distortion is more sensitive to the pulsating flow conditions in the baseline volute. This is due to the different secondary flow pattern in the cross-sections, hence demonstrating a direction for desired volute cross-sectional shape to be used in a turbocharger radial turbine for internal combustion engine.